Comparative Analysis of Stock Price Index Before and After The Announcement of Silicon Valley Bank (SVB) Bankruptcy - Ayu Puspitasari (AJAR, 2024)
The recent bankruptcy of Silicon Bank Valley (SVB) has sent shockwaves globally, given SVB’s status as a top-16 bank in the United States specializing in financing startups. The collapse of SVB has ignited concerns about a potential crisis, prompting a crucial research initiative to assess the likelihood of such a scenario. Since SVB’s bankcruptcy announcement, a notable occurence has been the sustain depression of the Composite Stock Price Index (IHSG) for several days. Consequently, this study aims to scrutinize and assess whether there are statistically significant variations in the stock price index before and after SVB’s bankcrupty announcement, not only within Indonesia but also throughout the ASEAN region. Utilizing quantitative approach, this research relies on secondary data in the form of stock price indices from multiple ASEAN stock exchanges. The observation period spans 14 days before and after March 10, 2023 (the announcement date). The analysis reveals that the stock price indices of JKSE, SETI, KLSE, and STI exhibited significant variations before and after the SVB announcement. However, the PSEI stock price index demonstrated no discernible differences. These findings shed light on the potential interconnectedness of SVB’s bankcruptcy with stock market movements in the ASEAN region.